The Impact of Sun Exposure Duration and Dietary Patterns on Vitamin D3 Levels in the Iraqi Population - Zainabkh. Abbas; Baidaa T. Ali; Marwah Ayad Al-Hamadani; Umelbaneen J. Alalawy; Mokhalad Gh. Azzawi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Vitamin D3 is a crucial nutrient involved in various physiological processes, including calcium absorption, bone health, immune function, and inflammation regulation Vitamin D deficiency is considered to be one of the most common medical conditions worldwide. Aim: to evaluate Levels of Vitamin D3 and its correlation with Sun Exposure Duration And Dietary Patterns at AL-Karama Hospital . Method: In this cross-sectional study, a sample of 500 persons was randomly selected from those who visited. The data collecting period spanned from April to October . It involved conducting direct interviews utilizing a specifically designed questionnaire for the study. The data was analyzed using the SPSS program, specifically version 24. A p-value is deemed significant if it is less than 0.05. Results:Males A significant proportion of males are deficient in vitamin D3 (22.8%), with 6.8% falling into the insufficient category and 3.4% classified as sufficient. Females A higher percentage of females are deficient (45.6%) in vitamin D3, with 13.4% falling in the insufficient category and 8% having sufficient levels.A large proportion of individuals consuming both types of food are deficient (59.2%), while 20% are insufficient and 11.4% are sufficient.Also a highly significant relationship between serum vitamin D3 levels and duration of sun exposure. Conclusion : Vitamin D deficiency appears to be more common in femalesAlso diverse diet that includes both plant and animal sources improves Vitamin D levels.Adequate sun exposure (at least 1 hour daily) is a critical factor for maintaining sufficient Vitamin D levels.